ANALISIS UNIT PENANGKAPAN IKAN PILIHAN DI KABUPATEN LAMPUNG SELATAN - Meizar Malanesia; John Haluan; Hartrisari Hardjomidjojo; Domu Simbolon (Buletin PSP, 2007)
Fisherie resources utilization in Residency of South Lampung as so far has faced on larger potency of fisheries capture while the management is not optimally done yet. This situation has indicated the low productivity of fishing units including the existing fleets as well as unsupported fishing gears facilities in traditional basis. In other hand, in general, the human resources are rare with low management capability. As consequence, technology transfer (adoption) to the lowest level fishermen is constrained. Fishermen slowly use existing technology and be more diversified in business activities. In addition, fishermen's access on capital loan is limited. This research conducted in marine region of South Lampung Residency. The required information is including potency of natural resources, human resources, institution, and available facilities. Data and information on fisheries will be prioritizing to analyze. The data analyses are including standardization of fishing unit, biological aspect analysis, environmental aspect, sustainability and financial feasibility. As we know, fishing units are technical unity in catchments efforts that usually consisted of the Fishermen, vessel and fishing gears. According to the analysis result on fisheries resources and selection on existing fishing units, the expected output should resolved specified for fisheries problems in the regency. In other hand, fishermen expected be to increase the production. Increasing on fisheries product will have significant impact on fisheries activities and fishermen's income. By improving the fishermen's income, the fishermen welfare will be improved.